2020
DOI: 10.1101/2020.09.21.20196428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sharing a household with children and risk of COVID-19: a study of over 300,000 adults living in healthcare worker households in Scotland

Abstract: Background Children are relatively protected from novel coronavirus infection (COVID-19). The reasons for this protection are not well understood but differences in the immune response to Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) have been implicated. If such differences are due to differential exposure to non-SARS-CoV-2 infectious agents, adults who are close contacts of children may partly share in this protection. Such a protective effect would have important implications for the lives of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
(49 reference statements)
3
10
0
Order By: Relevance
“…One previous cohort study of 310,097 healthcare workers and other adults in their household in Scotland has also addressed whether the risk of SARS-CoV-2 infection and severe outcomes from COVID-19 differs between adults living in households with and without children aged 0 to 11 years. 21 Similar to our results they find no increase in hospitalisation due to COVID-19 for people living with young children. However, they find a slightly reduced rate of testing positive for COVID-19 for adults living with young children, and evidence that the protective effect increased with a greater number of children.…”
Section: Discussionsupporting
confidence: 90%
“…One previous cohort study of 310,097 healthcare workers and other adults in their household in Scotland has also addressed whether the risk of SARS-CoV-2 infection and severe outcomes from COVID-19 differs between adults living in households with and without children aged 0 to 11 years. 21 Similar to our results they find no increase in hospitalisation due to COVID-19 for people living with young children. However, they find a slightly reduced rate of testing positive for COVID-19 for adults living with young children, and evidence that the protective effect increased with a greater number of children.…”
Section: Discussionsupporting
confidence: 90%
“…We and others have previously reported lower risk in teachers compared with others of the same age and sex [7,14]. The inverse association of severe disease with the number of school-age children in the household extends and confirms the findings of an earlier study of health care workers and their families [15]. In the OPENSAFELY cohort, the rate ratio for fatal COVID-19 associated with living with children aged 0-11 years was 0.75 after adjusting for covariates, but no dose-response relationship was reported [16].…”
Section: Association With Household Compositionsupporting
confidence: 86%
“…An important finding of our study is that participants living with children under the age of 12 were clearly less likely to be seropositive. A large study among over 300’000 HCW households from Scotland has recently found a similar association 17 . In contrast to the Scottish study, we corrected our result for important confounders, including age of HCW, full-time working, and leisure activities.…”
Section: Discussionmentioning
confidence: 82%